(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The value of financial derivatives comes from an underlying asset or benchmark. The Indian derivatives market has grown rapidly since 2000, offering a wide choice of derivative instruments to manage risk, speculate on price changes, and diversify portfolios. This essay discusses financial derivatives in the Indian derivatives market, covering their underlying assets, risk management applications, types of derivatives, market players, regulation, and economic impact. Indian derivatives market financial derivatives are thoroughly examined in this paper. The report evaluates the market, various derivatives instruments, and their impact on the Indian economy. Financial reports, scholarly journals, and government publications provide secondary data. Financial derivatives help market players hedge against price changes and reduce losses, according to the research. It examines derivative trading in equities, commodities, and currencies and market liquidity and depth. The report also analyses India’s derivatives trading regulatory system for market integrity and transparency. Over the years, India has had great success with equity derivatives. The study examined the derivative market over time and compared the NSE and BSE using percentage analysis, trend, and CAGR.